SHARIA COMPLIANCE : Analytical Study of Mudharabah Agreements in BMT UM Sarolangun District - Asmo, Abdi; Anggraini, Misi (Jurnal Studi Islam dan Sosial, 2023)
This research discusses compliance with sharia principles which is an absolute requirement that must be implemented by financial institutions that implement sharia principles. This research uses descriptive qualitative methods. The results of the research show that the implementation of the Mudharabah  contract product at BMT UM Sarolangun Regency is said to be in accordance with sharia compliance standards, considering the results of the analysis regarding implementation at BMT UM Sarolangun Regency in KHES article 248 regarding for contract implementation and is confirmed by the opinion of the sharia supervisory board that implementation in the contract Mudharabah  at BMT UM Sarolangun Regency is in accordance with sharia compliance through analysis carried out by the supervisory board using general and internal regulations. Regarding the distribution of results, if it is concluded from the previous discussion, it can be said that the BMT UM Sarolangun Regency is in accordance with Sharia Compliance. If you look at the Compilation of Sharia Economic Law, among other things, article 236 regarding the percentage of distribution of business results is stated as clear and certain.